Implementasi Aksi Nyata Guru Penggerak Pasca Pendidikan Program Guru Penggerak di SMKN 2 Pandeglang Provinsi Banten - Agustina, Lisa; Maritasari, Donna Boedi; Meka, Lesly Martha Cecilia (Educatio, 2025)
This research was conducted to determine whether the Implementation of Real Action carried out by Post-Education Leading Teachers of the Leading Teacher Program at SMKN 2 Pandeglang, Banten Province was still carried out optimally and sustainably even though the Leading Teacher Program Education that had been carried out by Leading Teachers at SMKN 2 Pandeglang had been completed. Real Action is part of a series of MERDEKA Learning that is studied and must be carried out in schools to provide a positive impact on the school ecosystem by Prospective Leading Teachers while participating in the Leading Teacher Program Education. Do Leading Teachers continue and develop the Real Actions they carry out after Leading Teacher Education? This prompted researchers to conduct a study entitled Implementation of Real Action of Leading Teachers Post-Education Leading Teacher Program Education at SMKN 2 Pandeglang, Banten Province. This research was conducted using a descriptive qualitative research method, data collection was carried out through purposive sampling techniques with In Depth Interviews through source triangulation techniques, namely leading teachers, fellow leading teachers and students. The results of the research that has been conducted found that the Real Actions carried out by the Leading Teachers during the Leading Teacher Education Program are still consistently carried out and even develop with other new Real Actions and have a positive impact on the school ecosystem at SMKN 2 Pandeglang, Banten Province and provide a systemic impact for other schools that work together in adapting and developing the Real Actions carried out by Leading Teachers through the SMK Teachers Association in Pandeglang Regency, Banten Province.